The microstructure analysis of white etching layer on treads of rails. (December 2017) - Pan, Rui; Ren, Ruiming; Chen, Chunhuan; Zhao, Xiujuan
Abstract: Through the utilization of the scanning electron microscope (SEM) and transmission electron microscope (TEM), the microstructure of Martensite White Etching Layers (WELs) on the surface of treads of U71Mn rail(used for a long time and taken from curves of normal railroad tracks) was analyzed and also its formation mechanism was discussed. As the result showed, the WELs observed from the cross-section was crescent-shaped and discontinuously distributed, with the thickness between 30 and 100 μm. Within the microstructure of WELs, the grain size of prior austenite at high temperature was ultra-fine, with the maximum diameter of approximate 1 μm at the outermost layer. As depths increased in the WELs, the grain size of prior austenite inside the WELs gradually became smaller; when the temperature on rail surface reached the temperature of austenitic transformation, austenite grains were less than 200 nm. Under the condition of room temperature, the microstructure inside the WELs was mainly composed of martensite. However, nanocrystalline α-phase, the structure of which was body-centered tetragonal, existed within 300 nm in the outermost layer of the WELs, and its misorientation generally featured random distribution. The organizations in the subsurface of the WELs were plate martensite, and undissolved and ultra-fine cementite, the amount of which rose as depths increase. The formation of the above-mentioned WELs was caused by rapid temperature rises and the subsequent cooling down of rail surface when a train suddenly braked or crept on a track. Graphical abstract: Highlights: Through the special method, prior austenite boundaries and martensite inside WELs were observed by SEM. Inside WELs，the size of prior austenite grains was small and at the two-phase region it was only 200 nm. Nanocrystalline α-phase, with random misorientation, existed within 300 nm in the outermost layer.